SPADE: Geometry Learning Model within Elementary School - Epon Nur'aeni; Oyon Haki Pranata; Muhammad Rijal Wahid Muharram; Ika Fitri Apriani (Universitas Pendidikan Indonesia (UPI), 2020)
This research was initiated by a problem in learning geometry in primary schools, namely the use of learning models that tend to be monotonous and less attractive to students. In addition, the research is based on efforts to preserve existing cultures in Indonesia, especially those from Kampung Naga, Tasikmalaya, West Java Province. Kampung Naga is an area that still maintains traditional life and cultural wealth. Based on these conditions, research was carried out to solve problems through the development of the SPADE as a geometry learning model in elementary schools. SPADE stands for five activities, namely singing, playing, analyzing, discussing, and evaluating.Research development model by Plomp was used on this project. The research was conducted for three years and involved lecturers, students, teachers, and primary school students in Tasikmalaya City, West Java Province. The research instruments used were observation sheets, interview guidelines, learning assessment sheets, learning implementation videos, questionnaires, and field notes. The data were analyzed interactively with the following activities: 1) data reduction; 2) data presentations; 3) data verification. The research finds that SPADE is relevant as a learning model and got a positive response to be implemented in primary school. The SPADE learning model is expected to be implemented in a broader scope.